1991
DOI: 10.1038/icb.1991.12
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of macrophages, B cells and splenic dendritic cells as antigen‐presenting cells in West Nile virus‐specific murine T lymphocyte proliferation

Abstract: Summary I nihis paper, the relative efficacy of macrophages, B cells and splenic dendritic cells (SDC) in presenting West Nile virus (WNV) antigens to WNV memory CD4"'' T cells is examined. The results indicate that, under appropriate conditions, all these ceil types can function as antigen-presenting cells (APC). Li.sicria-mduccii peritoneal macrophages induced higher proliferativc responses than SDC or B cells derived from naive or 14 day WNV-primcd mice. The ability of Z.mma-induced macrophage populations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…The lack of CD4 ϩ and predominance of CD8 ϩ T cells in CNS infiltrates has been observed previously in flavivirus infections (34) and in other viral infections of the CNS, such as lymphocytic choriomeningitis virus infection (8), but no satisfactory explanation has been advanced so far which is able to explain the prevalence of one type of T effector cells over the other. B6 mice are genetically fully competent to respond to WNV antigens, with a vigorous CD4 ϩ T-cell response in the periphery (30). For two reasons, it also seems improbable that the lack of ligand for CD4 ϩ T cells (MHC class II) is responsible for this CD8 ϩ T-cell predominance, as has been proposed by Liu et al (34).…”
Section: Discussionmentioning
confidence: 89%
“…The lack of CD4 ϩ and predominance of CD8 ϩ T cells in CNS infiltrates has been observed previously in flavivirus infections (34) and in other viral infections of the CNS, such as lymphocytic choriomeningitis virus infection (8), but no satisfactory explanation has been advanced so far which is able to explain the prevalence of one type of T effector cells over the other. B6 mice are genetically fully competent to respond to WNV antigens, with a vigorous CD4 ϩ T-cell response in the periphery (30). For two reasons, it also seems improbable that the lack of ligand for CD4 ϩ T cells (MHC class II) is responsible for this CD8 ϩ T-cell predominance, as has been proposed by Liu et al (34).…”
Section: Discussionmentioning
confidence: 89%
“…Preliminary experiments described in detail elsewhere (2) established that priming mice i.v. with 10« p.f.u.…”
Section: Resultsmentioning
confidence: 99%
“…B cells obtained from three different sources were evaluated for their APC function in the stimulation of WNV-immune CD4+ T cells at four different S : R ratios ranging from 2.0 to 0.25 in two-fold steps. In earlier studies it was observed that WNV-specific T cell proliferative responses were suppressed at a 1/4 dilution of WNV antigen when B+ + + + cells were used as APC (2). Therefore more dilute (1/16) WNV antigen was used to pulse these APC.…”
Section: The Influence Of Apc Numbers On the Proliferation Of Wnv-spementioning
confidence: 99%
See 1 more Smart Citation
“…Our study focused on the two principal players: the T-lymphocytes and the DCs. DCs are the most powerful antigen-presenting cells, with a capacity of antigen-presentation that is hundreds of times more efficient than B lymphocytes and macrophages (29). They can activate resting T-cells and induce the generation of antigen-specific cytotoxic T-lymphocytes, which are the initiators of the immune response (30).…”
Section: Discussionmentioning
confidence: 99%